Building Leadership for e-Busines Development - Hanna, James (World Bank, Washington, DC, 2012)
Electronic business is becoming an essential component of private sector development in a growing range of nations to achieve and maintain international competitiveness. This is due basically to its multiple benefits as a strong driver of innovation, productivity improvements, lower transaction costs with governments, and poverty reduction. Experience shows that accelerating ebusiness adoption, particularly among smaller firms, requires deliberate leadership on the part of governments in conjunction with the private sector to establish a conducive policy framework and overcome market failures.